IDENTIFICATION OF THERAPY PROFILE AND FACTORS RELATED TO INCIDENCE OF PULMONARY TUBERCULOSIS IN DENPASAR-BALI - Hanum, Anisa; Jaya, Made Krisna Adi; Bakta, I Made (Journal Pharmaceutical Science and Application, 2020)
Background: Tuberculosis is a problem for millions of people around the world. Indonesia as the second biggest country with the highest number of Pulmonary Tuberculosis that treatment has improved gradually. Denpasar is a city with the highest sufferers in Bali. It’s caused by the high rate of population, dense human settlement, and other related factors. Objective: Profiling incident and pulmonary tuberculosis treatment in Denpasar City primary health care. Methods: Observational study with cross-sectional analytic approaches. Forty pulmonary tuberculosis patients and  One hundred twenty non-tuberculosis patients were observed in this study. Those were taken by multistage random sampling. Data were collected from medical records and questionnaires. A Chi-Square test was used for analyzing data. Results: Pulmonary tuberculosis sufferers are in productive ages which 65% were men. The treatment profile was excellently seen from the final treatment results of 31 people recovered and 9 people with complete treatment. Factors that have a statistical relation with pulmonary tuberculosis were occupation (p=0,012), income (p=0.003), smoking behavior (p=0.001), and contact history (p=0.001). The other factors with no relationship were education (p=0.270) and occupancy density (p=0.540). Conclusion: Pay attention to the caused factors of tuberculosis infection; society is suggested to implement a healthy lifestyle, maintain home sanitation, and environment. Keywords : Factor Related, Pulmonary, Tuberculosis, Primary Health Care, Denpasar City